2012
DOI: 10.1002/hbm.21504
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral reorganization of posterior temporal cortices in post‐lingual deafness and its relation to cochlear implant outcome

Abstract: Post-lingual deafness induces a decline in the ability to process phonological sounds or evoke phonological representations. This decline is paralleled with abnormally high neural activity in the right posterior superior temporal gyrus/supramarginal gyrus (PSTG/SMG). As this neural plasticity negatively relates to cochlear implantation (CI) success, it appears important to understand its determinants. We addressed the neuro-functional mechanisms underlying this maladaptive phenomenon using behavioral and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 54 publications
9
57
0
1
Order By: Relevance
“…They found that, when doing a rhyming task with written words, CI users with later good speech understanding showed an activation pattern that was consistent with them using the normal phonological pathway to do the task, whereas those with poor outcomes used a pathway normally associated with lexical-semantic understanding (Lazard et al 2010). They further compared activity evoked by speech and non-speech imageries in the right and left posterior superior temporal gyrus/supramarginal gyrus (PSTG/SMG) (Lazard et al 2013). These areas are normally specialised for phonological processing in the left hemisphere and environmental sound processing in the right hemisphere.…”
Section: Deafness Language and Brain Plasticity: Evidence From Imagimentioning
confidence: 99%
“…They found that, when doing a rhyming task with written words, CI users with later good speech understanding showed an activation pattern that was consistent with them using the normal phonological pathway to do the task, whereas those with poor outcomes used a pathway normally associated with lexical-semantic understanding (Lazard et al 2010). They further compared activity evoked by speech and non-speech imageries in the right and left posterior superior temporal gyrus/supramarginal gyrus (PSTG/SMG) (Lazard et al 2013). These areas are normally specialised for phonological processing in the left hemisphere and environmental sound processing in the right hemisphere.…”
Section: Deafness Language and Brain Plasticity: Evidence From Imagimentioning
confidence: 99%
“…With lower WMC, the option to engage working memory processing to compensate for phonological decline is likely to be relatively reduced as fewer resources are available for careful phonological analyses. Resorting to a whole word, lexico-semantic based route to word phonology may then be an alternative way to compensate for degraded representations (Lazard et al, 2010;Lazard et al, 2012). Such a strategy is likely to interfere with rhyme judgment but enhance recall via increased attendance to semantic rather than phonological features (Craik & Tulving, 1975;Morris, Bransford, & Franks, 1977;.…”
Section: Resultsmentioning
confidence: 99%
“…The reorganization likely reflects an increased responsiveness to visual stimuli in the left temporal cortex together with recruitment of the right temporal cortex for phonological processing (Lazard et al, 2011;Lazard et al, 2010;Lazard et al, 2012). While fMRI studies have indicated topographical changes in phonological processing following acquired HI, the time-course of these changes has not been examined previously.…”
Section: Purposementioning
confidence: 97%
See 1 more Smart Citation
“…In normal hearing older adults, lip and word reading broadly activate the abovementioned dorsal articulatory and spectrotemporal/phonological analysis networks, with the exception of the primary auditory cortices due to diminished auditory function [25]. SNHL adults engage a similar network, but exhibit greater amplitudes in the attendant structures, especially the prefrontal and premotor cortices, and recruit additional structures including the right posterior temporal lobe [21,[26][27][28], which is normally only activated by actual sounds [25].…”
Section: Introductionmentioning
confidence: 99%